Global Research Trends on Religious Tolerance and Interfaith Dialogue: A Bibliometric Review (2000–2025) - Muhamad Dupi; Fuad Dhiya Ul Husaen (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
The emergence of intolerance, social fragmentation and religiously driven violence over the last two decades demonstrates how the growing intricacy of religious variety and the inability of religious conflicts to subside in the 21st century has augmented scholarly debate on religious tolerance and interreligious dialogue as a tool of peaceful coexistence. Despite the increased pace in the development of research in this area, there is no full understanding of the trends in global research, the actors that contributed to it and the trends in its focusing. The purpose of this research is to map the trends and key actors in the research and networking of Religious Tolerance and Interfaith Dialogue all over the world in the period between 2000 and 2025. The research uses bibliometric review as a methodology and includes English-language journal articles that are available in the Scopus database. VOSviewer was used to analyze the bibliographic relationships between countries, institutions, journals, authors, publications and the co-occurrence of key words with network, overlay and density visualization to analyze 2,294 articles. The findings indicate a major growth in academic publication, especially following 2015 with 2023 being the highest point. The United States and the United Kingdom come out as the most influential contributors and Indonesia is a notable and emerging contributor in the Global South. Georgetown University and Harvard University are recognized as best institutions and Religions is the most fruitful journal. The analysis of the key word reveals that there are four broad thematic categories, including diversity and spirituality, socio-political and human rights aspects, contextual studies that involve Indonesia and theological-comparative studies. To summarize, the current paper has shown that a bibliometric review exposes the strategic information regarding the intellectual framework and emerging emphasis of interfaith research in favor of evidence-based academic research and policy formulation to enhance religious tolerance in the multicultural communities.